Antara Kaya dan Hina dalam Prespektif Filsafat Ekonomi Islam: Posisi Harta dalam Pembelajaran Hidup (Perspektif Pendidikan Islam) - Musfiqoh, Siti (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
Experts agree that the theory and practice of education should be based on thebasic conception of human beings, including the economic role therein. Educationis a symptom and human needs. In the sense that if someone does not get aneducation, then they will not be a real human being and will not be able to fulfillits function as a human being useful in life and living. The final goal of the HumanEssence in Islamic education is to create men in the concept of a perfect Moslemal-insan al-kamil, the man who always constancy and skilled in the functioningcontinuum of physical and their spiritual power to always be submissive andobedient to the holy God Almighty.